Tombs and landscapes in a canyon of the al-Ḥajar mountains: Results of the surveys at WTN07 in the Tanūf District (North-Central Oman), 2022–2023 - Kuronuma, Taichi; Tanabe, Kantaro; Miki, Takehiro; Kondo, Yasuhisa (Proceedings of the Seminar for Arabian Studies, 2024)
Research towards the reconstruction of various archaeological landscapes in the Al-Ḥajar mountains is still ongoing. Past investigations in the Wādī Tanūf canyon have revealed long-term transformation of landscapes of higher places, such as hilltops and a cave on a cliff. However, the function of the wadi terraces has not been sufficiently investigated. In the 2022–2023 season, we surveyed the site of WTN07 on a wadi terrace and documented 123 Islamic graves, as well as one probable Wādī Sūq tomb (Tomb 122). A detailed examination indicates that Tomb 122 is a rare collective tomb in North-Central Oman and has composite characteristics represented by a U-shaped chamber, a possible entrance corridor, and an attached annex with a few subsidiary tombs. Furthermore, we have identified eight non-mortuary features, including a newly discovered building (Structure 01) in Wādī Tanūf, as well as a platform (Structure 02) and a long wall (Structure 04). These findings highlight the importance of the terrace in the canyon, given the limited flat space available. We assume that the small terrace running along the river was a place for different activities over time, with most of the evidence related to the movement of people in the trans-Ḥajar region, since the canyon can be considered as a corridor.